The Influence of Marshel Widyanto as Brand Ambassador of Ms Glow's Brand Image - Muhammad Jhorgi Dafitra; Indria Angga Dianita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Men have started to realize the importance of facial care. As a result, various male-only skin care products and services are increasing being distributed and demanded by the general public. Ms Glow ranks first in sales in May 2021 with the sales of MS Glow facial treatment category reaching 74.82 billion Rupiah. In mid-2021, MS Glow for Men announced that Marshel Widyanto became their brand ambassador. This research was conducted with the aim of knowing how much influence Marshel Widyanto as a Brand Ambassador has on the MS Glow Brand Image in Indonesia. This study uses the independent variable, namely Brand Ambassador with sub-variables Visibility, Credibility, Attraction, and Power. The dependent variable is Brand Image with Strength, Favorable, and Uniqueness sub-variables. This research was conducted using quantitative methods with descriptive research type. The sampling technique used in this study is probability sampling, with simple random sampling technique, and the analysis technique uses normality test, heteroscedasticity test, correlation coefficient test, coefficient of determination, simple linear regression, and hypothesis testing using T test. Based on the results of the study, Brand Ambassador Marshel Widyanto has an influence on the Brand Image of MS Glow by 86.1%, and the remaining 13.9% is influenced by other factors which are not examined in this study.